Genetic diversity and phylogenetic relationships within local pigs in southern Benin - ADOUKONOU SAGBADJA, Hubert (My University, 2021)
The current context of climate change requires the conservation of local zoogenetic resources already very well adapted to the traditional breeding system, rough feeding, and heat and cold stress. This study assessed genetic diversity in local pigs in southern Benin, as a prerequisite for their sustainable use and sustainable management in Benin. A total of 69 individuals including 54 local pigs, 7 Large-White, and 8 hybrids (local pigs×Bush-pig) were genotyped by using 17 microsatellite markers. On the average, 8.94 alleles were detected per locus. Average expected and observed heterozygosities were respectively 0.51 and 0.46. Polymorphic information content was 0.61, and genetic diversity was 0.53. A phylogenetic tree gathered local pigs into three genetic clusters. Genetic structural analyses revealed introgression of Large-White’s genes into the local pig’s genome. Three groups were identified: hybrids (subpopulation 1), a mixture of Large-White and local pigs (subpopulation 2), and only local pigs (subpopulation 3). Symmetrical allelic distances were higher between subpopulations 1 and 2 (0.787) and then 1 and 3 (0.713). The same trend was detected for genetic distances between pairs of subpopulations. Genetic differentiation between subpopulations 2 and 3 was very weak as a consequence of high gene flow (10.82). Molecular variance analysis showed that 77% of genetic diversity within populations was related to variability between the individuals. These results showed that local pigs in southern Benin are threatened by genetic erosion and suggest prompt actions to implement sustainable conservation strategies.
Keywords: Benin · Conservation · Introgression · Local pigs · Microsatellite markers · Molecular genetics